+0  
 
+5
198
1
avatar

My solution was: -.3, which is wrong...

The right solution should be: 1.3

 

I followed these steps:

 

2*(1/3)^(0.3-x)-4=2

2*(1/3)^(0.3-x)=-2

(1/3)^(0.3-x)=-1

(1/3)^(0.3-x)=-(1/3)^0

0.3-x=0

x=.3

Guest Feb 14, 2017
edited by Guest  Feb 14, 2017
edited by Guest  Feb 14, 2017
 #1
avatar+87293 
0

2*(1/3)^(0.3-x)-4=2  add 4 to both sides

 

2*(1/3)^(0.3-x) = 6     divide both sides by 2

 

(1/3)^(.3 - x)  = 3      

 

Note......  (1/3)^(.3 - x)  = 1 / [ 3^(.3 - x)] =   3^[ - ( .3 - x)]   = 3^(x - .3)

 

3^(x - .3)  = 3^1        equate exponents

 

x - .3  = 1     add .3 to both sides

 

x  = 1.3

 

 

cool cool cool

CPhill  Feb 14, 2017

5 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.